The Visit of Moro Islamic Community Leaders to Indonesia - Tim PPIM UIN Jakarta (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This program consisted of a visit by Moro leaders to I Indonesia and was organized by PPIM UIN Jakarta in cooperation with the Australian Embassy. The duration of visit was ten days, from 17-26 November 2008. The visit was intended to strengthen relations between the Muslim communities in the Southern Philippines and Indonesia in the area of conflict resolution and the constructive role Islamic institutions can play in a pluralist, democratic state. It also aimed to enhance public awareness through the media, thereby reinforcing these values among the general public. The visit was also aimed to develop options for further cooperation between these communities.DOI: 10.15408/sdi.v16i1.494